Patient-reported outcomes in lung cancer surgery: A narrative review - Hang Yi; Xu Ou-Yang; Qian Hong; Lu Liu; Man Liu; Yan Wang; Guochao Zhang; Fengyan Ma; Juwei Mu; Yousheng Mao (Asian Journal of Surgery)
Lung cancer is a leading cause of cancer-related mortality worldwide, profoundly affecting patients' quality of life. Patient-reported outcomes (PROs) provide essential insights from the patients' perspective, a crucial aspect often overlooked by traditional clinical outcomes. This review synthesizes research on the role of PROs in lung cancer surgery to enhance patient care and outcomes. We conducted a comprehensive literature search across PubMed, Scopus, and Web of Science up to March 2024, using terms such as ''lung cancer,'' ''Patient Reported Outcome,'' ''lobectomy,'' ''segmentectomy,'' and ''lung surgery.'' The criteria included original studies on lung cancer patients who underwent surgical treatment and reported on PROs. After screening and removing duplicates, reviews, non-English articles, and irrelevant studies, 36 research articles were selected, supported by an additional 53 publications, totaling 89 references. The findings highlight the utility of PROs in assessing post-surgical outcomes, informing clinical decisions, and facilitating patient-centered care. However, challenges in standardization, patient burden, and integration into clinical workflows remain, underscoring the need for further research and methodological refinement. PROs are indispensable for understanding the quality-of-life post-surgery and enhancing communication and decision-making in clinical practice. Their integration into routine care is vital for a holistic approach to lung cancer treatment, promising significant improvements in patient outcomes and quality of care.